The call number: A guide to varied materials: Videotape script - Merriman, Stella (UWI, UNESCO, UNICEF, UNDP, RLA/142, 1973)
This manual is a guide to varied materials. It serves to provide instructions on how to use the card catalogue to locate books on the library shelves and also to identify the type of material by the catalogue card.
The Card Catalogue
Keywords: Educational technology